2011
DOI: 10.1007/s10327-011-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated plant viruses: preventing virus diseases and understanding the molecular mechanism

Abstract: Attenuated viruses have been isolated and studied not only as a practical means of controlling virus diseases but also to gain a molecular understanding of viral virulence and cross protection. They have been isolated from crop fields and generated through high/low temperature treatment or by mutagens such as nitrous acid and ultraviolet irradiation. Some viruses have been beneficially used in fields and evaluated for one or more decades. Molecular genetic studies on attenuated viruses have revealed that amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 74 publications
0
23
0
1
Order By: Relevance
“…Alignment of the amino acid sequences of CGMMV-SH and CGMMV-SH33b revealed that five amino acid substitutions were found between the two virus strains: Gly at amino acid residue 480, Val at 1124, Asp at 1157 and Ser at 1397 of RP, and Val at 156 of CP for Glu, Ala, Asn, Pro and Ala in CGMMV-SH, respectively (Tan et al 1997). Although different tobamoviruses are known to be attenuated by the mutations in the replicase gene, none of the mutations are commonly found in different tobamoviruses (Nishiguchi and Kobayashi 2011).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Alignment of the amino acid sequences of CGMMV-SH and CGMMV-SH33b revealed that five amino acid substitutions were found between the two virus strains: Gly at amino acid residue 480, Val at 1124, Asp at 1157 and Ser at 1397 of RP, and Val at 156 of CP for Glu, Ala, Asn, Pro and Ala in CGMMV-SH, respectively (Tan et al 1997). Although different tobamoviruses are known to be attenuated by the mutations in the replicase gene, none of the mutations are commonly found in different tobamoviruses (Nishiguchi and Kobayashi 2011).…”
Section: Discussionmentioning
confidence: 94%
“…This phenomenon has been successfully used to protect crops against severe viruses in tomato, melon and pepper plants in Japan (Nishiguchi and Kobayashi 2011). The phenomenon is virus specific and it works only between strains of the same virus and related virus species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported by McKinney, who observed that tobacco plants preinfected with a mild variant of Tobacco mosaic virus (TMV) were protected from infections by a severe TMV strain (21,37). Similar observations have since been made with many other viruses, leading to the adoption of cross-protection to control viruses such as Citrus tristeza virus, Papaya rinspot virus, Zucchini yellow mosaic virus (ZYMV), and Potato virus X (PVX) (4,5,24,32,34).…”
mentioning
confidence: 99%
“…Mild strains may be obtained either as natural occurring variants (as ZYMV-WK) or after various treatments including high or low temperature, nitrous acid, or UV irradiation treatments (Fuchs, Ferreira, et al, 1997;Lecoq, 1998;Nischiguchi & Kobayashi, 2011). After a combination of these treatments, mild strains of CMV, CGMMV, PRSV, WMV, and ZYMV have been obtained and tested under field conditions.…”
Section: Other Mild Strains Of Cucurbit Virusesmentioning
confidence: 99%